EFEKTIFITAS PERATURAN MAHKAMAH AGUNG TENTANG PROSEDUR MEDIASI TERHADAP PERAN MEDIATOR DI PENGADILAN AGAMA SIDOARJO - Achmad Syaifudin (AL-HUKAMA, 2017)
This paper intends to compare the effectiveness of Supreme Court Regulation no. 1 of 2008 and Supreme Court Regulation no. 1 of 2016 about mediation procedures to mediators’ role in Religious Court of Sidoarjo. By the documentation and interview techniques, this paper found that mediators in the Religious Courts of Sidoarjo became a facilitator in solving problems or disputes to reach favorable agreement for the parties. There is a difference between Perma No. 1 of 2008 with Perma No. 1 of 2016, namely the shorter duration of mediation, the obligation for the parties to attend directly the mediation meeting, and the existence of rules of good faith in the mediation process and its legal consequences. These differences are quite helpful in facilitating the mediation process, but there is no significant change in success rate prevention of divorce due to lack of good faith from the litigants. The Sidoarjo Religious Court should socialize Perma No. 1 of 2016 on mediation procedures to mediators and the parties of the dispute. Mediators in the Religious Courts of Sidoarjo should understand and apply correctly the existing rules in Perma No. 1 of 2016 on Mediation Procedures.